Preoperative Bariatric Surgery Utilization Is Associated With Increased 90-day Postoperative Complication Rates After Total Joint Arthroplasty. Issue 5 (1st March 2020) - Liu, James X.; Paoli, Albit R.; Mahure, Siddharth A.; Bosco, Joseph; Campbell, Kirk A.
Abstract : Background: This study evaluates the incidence of bariatric surgery (BS) before total joint arthroplasty (TJA) in New York State and compares patient comorbidities and 90-day postoperative complications of patients with and without BS before TJA. Methods: The NY Statewide Planning and Research Cooperative System database between 2005 and 2014 was reviewed and 343, 710 patients with TJA were identified. Patients were stratified into the following three cohorts: group 1 (patients who underwent BS < 2 years before TJA [N = 1, 478]); group 2 (obese patients without preoperative BS [N = 60, 259]); and group 3 (nonobese patients without preoperative BS [N = 281, 973]). Principal outcomes measured were patient comorbidities, 90-day complication rates, length of inpatient stay, discharge disposition, mortality rate, and total hospital costs. Results: BS before TJA incidence increased from 0.11 of 100, 000 to 2.4 of 100, 000 from 2006 to 2014. Preoperative BS did not notably change the number of patient comorbidities at the time of TJA. Group 1 had more patients with 90-day complications (40.7% versus 36.0%, P < 0.001) than group 2. No difference was found between group 1 and the other groups in home discharge, pulmonary embolism, deep vein thrombosis, and mortality rates. Total hospital costs were higher for group 1 (18, 869 ± 9, 022 versus 17, 843 ± 8, 095, P < 0.001) compared with those for group 2. Conclusion: BS before TJA has increased annually over a 10-year period in New York State and is associated with greater 90-day postoperative complication rates and higher immediate hospital costs when compared with obese patients without BS.